THE TEACHER’S PERSONALITY IN EDUCATION: THE NEW ROLE OF THE MODERN EDUCATOR (British Journal of Global Ecology and Sustainable Development, 2025)
In an era of rapid educational change, the teacher’s personality has become one of the most significant factors influencing the learning process. This article explores how educators’ emotional intelligence, adaptability, and communication skills contribute to student development and the success of modern education systems. The paper emphasizes the teacher’s evolving role as a facilitator, mentor, and innovator in digital and multicultural learning environments.